IMPLEMENTATION OF MINOR MARRIAGE DISPENSATION IN THE SIDOARJO RELIGIOUS COURT - Rizki Kurniawan, Ryan; Sulistiyantoro, Hariyono (JARES (Journal of Academic Research and Sciences), 2024)
Religion and the State have regulated legal provisions regarding marriage, because marriage is a sacred act for every man and woman who wants to build a household with the aim of perfecting their religion and achieving a Sakinah, Mawaddah, Warrahmah family. Carrying out a marriage cannot be done haphazardly because marriage for humans has methods and rules determined by law, both in Islamic law and positive law. Underage marriage is a complicated problem and not a new phenomenon, underage marriage occurs not only in rural areas but in urban areas there are also similar cases, caused by many economic problems, low education, lack of understanding of certain cultures and religious values. , it can also be caused by promiscuity resulting in pregnancy outside of marriage. Underage marriages are a sensitive matter among society, underage marriages are carried out because promiscuity is still rampant which results in out-of-wedlock pregnancies and underage marriages are carried out to cover up disgrace and the child being conceived has a clear status. This research aims to focus more on the process of implementing the underage marriage dispensation in the Religious Courts. Empirical research methods. This research shows that underage marriages still exist and the number is still large in relation to applications for dispensation for underage marriages at the local Religious Court.